Optimalisasi Kemampuan Numerasi Siswa Sekolah Dasar melalui Penerapan Model Problem Based Learning (PBL): Studi Literatur - Rizqi Nararya Pangesti; Kurnia Rahmawati; Marsa Anugerah Ibadilah; Salwa Destira Nurani; Rara Ardina Puspa Wardani; Ivo Engelina Puspitaningrum (Prosiding Konferensi Ilmiah Dasar, 2026)
This article examines the effectiveness of the Problem Based Learning (PBL) model in improving elementary school students' numeracy literacy through a literature review. Indonesian elementary students' numeracy skills remain low based on PISA and National Assessment (AN). This study used a literature review method with a descriptive qualitative approach on three national scientific articles obtained from Google Scholar, Garuda, and SINTA, selected based on publication within the last five years, a focus on PBL and numeracy literacy, and clear methodology, then analyzed through data reduction, data presentation, synthesis of findings, and conclusion drawing. Findings show that PBL is consistently effective across two different research designs, a systematic literature review and pre-experimental quantitative research: PBL combined with interactive media (YouTube, Wordwall, a spinning board, Math Playground) raised fifth-grade students' average AKM numeracy score from 37.73 to 81.14, while PBL combined with Wordwall raised third-grade students' numeracy literacy from 70.52 to 81.91. PBL's effectiveness is underpinned by strengthened cognitive ability, learning motivation, and self-efficacy, but is conditional on factors such as ICT integration, teacher-student relationships, and alignment with students' demographic background. It is concluded that PBL's success depends not only on the model itself but also on teachers' active role and on adapting instructional design to each school's context.